ENTERIC DUPLICATION CYST MIMICKING A MESENTERIC CYST WITH ELEVATED CYSTIC CEA: A RARE CASE REPORT (Asian Journal of Medical Research and Health Sciences, 2026)
Enteric duplication cysts (EDCs) are rare congenital gastrointestinal anomalies; those near the pancreatic tail are exceptionally uncommon. Nonspecific clinical and radiological features lead to misdiagnosis as mesenteric cysts. We report the case of a 16-year-old female presenting with a one-year history of left hypochondriac pain, vomiting, and a palpable abdominal mass. Ultrasonography and contrast-enhanced CT demonstrated a well-defined cystic lesion in the left hypochondriac region, favouring a diagnosis of mesenteric cyst, with EDC as a differential. Cystic fluid analysis revealed markedly elevated CEA. Laparoscopic exploration revealed dense adherence of the cyst to the pancreatic tail, necessitating conversion to a laparoscopic-assisted distal pancreatectomy with cyst excision. Histopathology confirmed a double-layered smooth muscle wall lined by gastric-type epithelium, fulfilling the Ladd and Gross criteria for EDC with gastric heterotopia. This case highlights the diagnostic difficulty of distinguishing EDC from pancreatic cystic lesions, emphasizing the importance of histopathology and intraoperative flexibility.